Telerehabilitasi pada Penyakit Paru Obstruktif Kronik - Tifany, Elisabeth Pauline; Tambunan, Tresia Fransiska Ulianna (PT Kalbe Farma Tbk., 2023)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of death worldwide. Pulmonary rehabilitation is an essential component of COPD management and can be delivered through telerehabilitation programs. COPD telerehabilitation consists of exercise testing and training that can be performed at home with supervision from a physiotherapist or remotely using a smartphone application. Exercise training includes cardiorespiratory endurance, resistance, flexibility, and respiratory muscle training. COPD telerehabilitation is effective in improving exercise tolerance, reducing the incidence of acute exacerbations, and improving patients’ quality of life.